Evaluation of analgesic use in physical trauma patients presenting to the emergency department of a tertiary care hospital: a cross-sectional study - Tuladhar, LR; Sharma, S; Hussain, S; Pokhrel, S; Dhamala, N; Awal, K (Devdaha Medical Journal, 2025)
Introduction: Effective pain management is essential in trauma cases to ensure patients' recovery and stabilization presenting to the emergency room. The objective of this study was to observe the prescription pattern, route of administration and compare pre- and post-analgesic pain scores among trauma patients presenting to the emergency department of a tertiary care hospital. The rationale of this study is to generate local evidence on analgesic prescription pattern, route of administration and changes in pain scores before and after analgesic use.Methods: This was a descriptive cross-sectional study to assess analgesic use in physical trauma cases at Nepal Medical College and Teaching hospital. The study was conducted from 1st January to 30th June 2024 following ethical approval from the Institutional Review Committee (reference number: 41-080/081). A total of 150 trauma patients admitted in the emergency department were observed. The sampling method used was convenience sampling. Data entry and analysis was done using Statistical Package for the Social Sciences version 16.Results: Among 150 trauma patients (73.3% male, mean age 32.4 ± 16.7 years), road traffic accidents were the most common cause (43.3%). Acetaminophen (45.3%) and diclofenac (44%) were the most frequently prescribed analgesics, mainly via intravenous (52%) and intramuscular (37.3%) routes. Analgesic administration led to a significant reduction in pain scores (numeric rating scale-NRS) across all baseline pain categories (Wilcoxon signed-rank test, p < 0.05), with the greatest reduction observed in patients with worst, severe, and moderate pain.Conclusion: Non-opioid analgesics effectively managed pain in trauma patients, with minimal opioid use. Intravenous and intramuscular administration were preferred for rapid pain relief. Adoption of multimodal strategies, including opioids, ketamine, or regional analgesia, could further enhance pain management in emergency settings.